Pengembangan Video Animasi Berbasis Aplikasi Adobe Premiere Pro CC 2019 Untuk Meningkatkan Kemampuan Membaca Siswa Sekolah Dasar - Siti Rohimah; Nurul Aini (Institut Nalanda, 2024)
The very rapid development of technology requires all aspects of life to move forward, according to technological developments. One aspect that is demanded is education. Learning media as an alternative medium for materials taught by teachers to students today must prioritize technology in every learning media used. In line with this description, this research will try to develop a learning media based on Adobe Premier Pro CC 2019 to improve the reading skills of elementary school students. The method used in this research is Research and Development (R&D) with the ADDIE model. The ADDIE model is used as a procedure in developing products. Data collection techniques use interviews and questionnaires. Interviews and questionnaires are used as instruments to determine the results of needs analysis, aspects of the feasibility of the product being developed, as well as student responses regarding the product being developed. In the final stage, a student response test is carried out to determine the quality of the product. The results of the research show that this research was successful in developing a product with a very feasible category, obtaining a feasibility score of 88.265. The final product review shows that this product is ready and suitable for use.